The Effect of Collaborative Strategic Reading (CSR) on Muhammadiyah University Students’ Reading Comprehension and Their Perceptions - Nur Lailatul Fithriyah; Ahmad Munjin Nasih; Nunung Suryati (Graduate School of Universitas Negeri Malang, 2022)
Abstract: Reading is a language modality in which the sense of urgency is palpable despite the task difficulty. This study examined the hypotheses that CSR improves reading comprehension and fosters positive perceptions of the implementations. The result supported that using CSR produced levels of reading comprehension superior to conventional teaching instruction. The analysis of posttest among the groups revealed 5.56 greater effects for students in the experimental group. The t-test also reported that students had favorable impressions about CSR implementation. They recognized some reading strategies of CSR which assisted them at most in elevating comprehension. Abstrak: Membaca merupakan modal Bahasa yang urgensinya sangat nyata namun penugasannya tidak mudah. Penelitian ini menjabarkan hipotesis yang menyebutkan bahwa CSR meningkatkan pemahaman membaca dan mencipatakan persepsi positif pasca implementasi. Hasil penelitian mendukung bahwa melalui CSR dapat menghasilkan tingkat pemahaman membaca yang lebih tinggi daripada pengajaran konvesional. Analisa posttes antar grup menunjukkan ada pengaruh sebesar 5.56 untuk mahasiswa kelas eksperimental. Uji t juga menemukan bahwa mahasiswa memiliki kesan yang positif tentang implementasi CSR. Mereka menyadari adanya beberapa strategi membaca pada CSR yang paling bermanfaat dalam peningkatan pemahaman.